Cáncer de ano incipientes e inaparentes - Matteucci, Pablo; Pittamiglio, Horacio; López Susviela, Julio; Viola, Alberto (Cirugía del Uruguay, 1982)
Incipient carcinoma of the anus does not infiltrante the esphinter while the unsugpected one have their origin in previous benign diseases, and are masquerading with them. 3 cases are reported. One was treated with local excision and in the other two radiotherapy was added.